2012
DOI: 10.4028/www.scientific.net/amm.236-237.1251
|View full text |Cite
|
Sign up to set email alerts
|

Estimation for Bearing Preload of Machine Tool Spindle Based on Vibration Signal

Abstract: A significant source of noise and vibration in high speed machine tool spindle is bearing induced vibration, which is caused by geometrical characteristics and interactions between rolling members with surface irregularities. In this paper, analytical approach was proposed to calculate the bearing internal load distribution of spindle, with consideration of the operating conditions. The influences of operating conditions to internal load distribution, contact angles were analyzed. Furthermore, the estimation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Li [45] determined the minimum working preload of bearing under non-gyro spinning assumption at high rotating status, deduced the relationship between dynamic preload and initial preload considering the influence of high speed and high temperature working conditions. Xu [46] employed the power spectrum density method to study the frequency response of the spindle under different preload and rotation speed, predicted the connection between frequency characteristics and the preload. Xu [47] indicated that motor current value, bearing vibration, temperature rise and preload varied with rotation speed when the constant pressure preload was applied.…”
Section: Multi-parameter Based Criterionmentioning
confidence: 99%
“…Li [45] determined the minimum working preload of bearing under non-gyro spinning assumption at high rotating status, deduced the relationship between dynamic preload and initial preload considering the influence of high speed and high temperature working conditions. Xu [46] employed the power spectrum density method to study the frequency response of the spindle under different preload and rotation speed, predicted the connection between frequency characteristics and the preload. Xu [47] indicated that motor current value, bearing vibration, temperature rise and preload varied with rotation speed when the constant pressure preload was applied.…”
Section: Multi-parameter Based Criterionmentioning
confidence: 99%